PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF UNTUK PESERTA DIDIK KELAS IV SEKOLAH DASAR - Aulia Sholihah; Nana Hendracipta; Odin Rosidin (Jurnal Genta Mulia, 2025)
This research is motivated by the lack of interesting and interactive learning media variations that can improve students' understanding and motivation towards learning materials. This study aims to develop interactive powerpoint learning media used in the learning process of grade IV elementary school students. The method used is research and development (R&D) with a 4D model consisting of 4 stages, namely: define, design, develop, and dissimimate. This study uses an instrument in the form of a questionnaire in collecting data, the lifting sheets used are: media expert questionnaire, language expert questionnaire, material expert questionnaire and student response questionnaire. The results of the media expert validation showed a percentage of 87.36% with the category "very feasible". The validation of language experts showed a percentage of 80% with the category "feasible". The validation of material experts showed a percentage of 95% with the category "very feasible. The response of students to the media was very positive, with a percentage value of 93.33% with the category "very good". Based on these results, the interactive powerpoint learning media developed is feasible to be used as a learning medium for grade IV elementary school students.